Thermally stable, low resistance Mg2Si0.4Sn0.6/Cu thermoelectric contacts using SS 304 interlayer by one step sintering. (April 2021) - Jayachandran, B.; Prasanth, B.; Gopalan, R.; Dasgupta, T.; D., Sivaprahasam
Graphical abstract: Highlights: Reliable Mg2 Si0.4 Sn0.6 /Cu contacts were fabricated in one-step hot press sintering using SS 304 interlayer. Without SS 304 layer, electrical resistivity of Mg2 Si0.4 Sn0.6 increases ∼60 % due to Cu diffusion during sintering. Cu/SS 304/ Mg2 Si0.4 Sn0.6 show specific contact resistance (rc ) of 6.1 ± 2 μΩ.cm 2 while preserving thermoelectric properties. SS 304 interlayered contacts maintains rc < 10 μΩ.cm 2 even after 15 days annealing at 723 K. Abstract: Device fabrication using Mg2 Si1-x Snx thermoelectric (TE) material for 600–800 K application requires stable and low resistance electrical contacts between TE legs and the electrodes. In this study, n- type Mg2 Si0.38 Sn0.6 Bi0.02 was hot-pressed with Cu electrodes in a single step, resulting in Cu3 Mg2 Si and Cu4 MgSn phases at the interface. Although the specific contact resistance ( rc ) across the interface was 4.4 ± 0.9 μΩ.cm 2, the electrical resistivity of the TE leg increased by approximately 60 % due to Cu diffusion through the interface. Incorporating the SS304 interlayer to prevent Cu diffusion increased rc to 6.1 ± 2 μΩ.cm 2 . Upon annealing at 723 K for 3–15 days, rc remained at <10 μΩ.cm 2 with an approximately 15 % decrease in the power factor. However, without SS304, rc increased to 41.5 ± 18 μΩ.cm 2, with 65 % reduction in the power factor. Thus, this work demonstrates the fabrication of thermally stable Cu/Mg2 Si0.4 Sn0.6 joints by using the SS304 interlayer in a single-step process.